Research note: Effects of Laminaria japonica polysaccharides on serum digestive enzyme activity in weaned piglets - Luo, T. Y.; Wu, Q.; Huang, Y.; Xu, Y. Q.; Guo, M. Y.; Wang, C. W. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
The study investigated how varying levels of Laminaria japonica polysaccharides (LJP) in weaned piglet feed influenced the activity of digestive enzymes in the serum. 120 healthy piglets of at 21 days were selected for the experiment and randomized to four treatment groups, each comprising five replicates of six piglets. In the experiment, LJP was added at 0 (control), 100, 200 and 400 milli-grams per kilogram (mg/kg) to the basal feed of four treatment groups for 21-day. A significant de-crease in serum protease activity was observed in the 200 mg/kg LJP group when compared to the un-treated group (P < 0.05). Adding LJP to the feed had a trend of increased serum lipase activity with increasing LJP concentrations, but these increases were not statistically significant (P > 0.05). Further-more, dietary supplementation with 400 mg/kg LJP to the feed was observed to result in the highest serum amylase activity. However However, the observed changes were not considered to be of statistical signifi-cance (P > 0.05). In conclusion, LJP has a positive effect on nutrient metabolism in serum.